The Development of Pre-service Science Teachers’ Pedagogical Content Knowledge Competencies through Integrated Supervision (MIEC Model) in Collaboration with School Partnership - Satthaphon, Siriphan; Khunnarong, Supada; Pancharoen, Warisa; Lamlert, Niroot (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research employs mixed methods with the following objectives: 1) to examine the current state and challenges of supervising pre-service science teachers, 2) to develop a supervision model for pre-service science teachers in collaboration with school partnership, and 3) to investigate the implementation of a supervision model on the pedagogical content knowledge competence of pre-service science teachers. The participants were 45 instructors and 33 cooperating teachers, along with 9 pre-service science teachers. Data were collected from a questionnaire, lesson plan evaluation form, PCK assessment form evaluated by teachers and students. Both quantitative and qualitative analyses were conducted. The research findings are as follows: 1) The top three activities that supervisors regularly perform are: a) Providing various channels for science teacher students to contact and ask questions, b) Observing teaching sessions, and c) Reviewing lesson plans before teaching. The least frequent activity was providing opportunities for peer observation among pre-service science teachers. 2) The developed supervision model, the MIEC Model, consists of four steps: 2.1 Meeting, 2.2 Implementation, 2.3 Evaluation, and 2.4 Conclusion. The model was refined based on suggestions from three experts through a focused group, and 3) The supervision model effectively developed students’ PCK competencies. Students performed best in learning management strategies, while the least was in student learning. Other components such as orientation to science teaching, learning assessment, and curriculum understanding, were moderate, respectively.